A Case of Rare Diffuse Alveolar Hemorrhage and Review of Literature. Issue 10 (14th August 2017) - Scollo, Viviana; Zanoli, Luca; Russo, Elisa; Distefano, Giulio; Rapisarda, Francesco
It is well known that some disorders can cause concomitant kidney dysfunction with lung involvement. These syndromes, characterized by the simultaneous presence of intra-alveolar hemorrhage and acute glomerulonephritis, are caused by numerous and variable disorders. The most frequent are the antineutrophil cytoplasmic antibodies (ANCA)-associated vasculitis and Goodpasture syndrome. A quick discerning of the underlying causes and initiation of adequate treatment is crucial to prevent acute respiratory failure and irreversible loss of renal function. We reported the case of a 33-year-old man having hemorrhagic alveolitis presenting a picture consistent with Goodpasture syndrome in the absence of anti-glomerular basement membrane (anti-GBM) antibodies or ANCA at lab test and a review of literature. This case highlights the need to consider the chances of falsely seronegative cases of anti-GBM disease, as well as the importance of using all available assay routine tests. These cases would appear indeed more common than before if just taken into consideration their existence. Several reports have shown false seronegatives especially in patients with relapses, in smokers, and in patients with predominantly pulmonary symptoms.